The Financial Reporting in the Public Sector: Implementing the SAKTI System at Indonesia’s Ministry of Finance - Putri Haryani; Wastiqah, Adya Anindya; Tsabitah, Haura Ha'ilah; Marulak, Jeremiah Noah; Rafita Dwi Noviyanti; Risma Kusuma; Rizky Ramarif Kuntara (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2025)
The complexity of financial management within the public sector requires accountability and sound governance to be ensured by a strong, transparent reporting system. This study seeks to probe the financial reporting system inside Indonesia’s Ministry of Finance since it uses the SAKTI system as one tool that increases efficiency and meets government rules. Data were gathered through observation, document analysis, and online interviews with staff members of the Secretariat General of the Ministry of Finance since they used a qualitative approach. The study finds that entities conduct financial reporting through a structured as well as phased manner. UAKPA starts with the data entry, and then UAPA prepares the report for them. Key policies like PMK 22/PMK.05/2022, PMK 232/PMK.05/2022, along with SOPs from PMK 131/PMK.01/2015 support the integrated use of the SAKTI application and SPAN. Such financial statements included things like the LRA, LPSAL, Balance Sheet, LO, LPE, LAK, and CaLK. Show to the effect that you adhere to Government Accounting Standards (SAP). This research conveys just a key message. The key message from this research is that the Ministry's reporting practices represent a model of integration, accountability, and transparency in public financial management that can serve as a reference for other government institutions.